Management of Overactive Bladder - Yudiati, Yudiati; Hasanah, Hasanah (International Medical Journal Corp. Ltd, 2024)
Background: The management of overactive bladder (OAB) has undergone significant evolution, with a growing recognition of the multifaceted nature of the condition and the need for personalized treatment approaches. Literature Review: (Ulahannan & Wagg, 2009) emphasize the complexity of OAB management, particularly in the elderly, where pharmacological treatments like anti-muscarinic agents play a crucial role in modulating bladder activity. However, (Gomelsky & R Dmochowski, 2010) highlight the limitations of these agents, particularly concerning patient adherence due to side effects, which is a critical issue that can hinder treatment efficacy. The introduction of mirabegron, a beta-3 adrenoceptor agonist, as discussed by (T Lee et al., 2013), offers a promising alternative with a more favorable side effect profile, potentially enhancing patient compliance. Conclusion: In conclusion, the management of OAB is characterized by a complex interplay of pharmacological and non-pharmacological treatments, necessitating a personalized approach to care. The literature underscores the importance of addressing patient adherence, exploring new therapeutic avenues, and integrating behavioral strategies into treatment plans. As our understanding of OAB deepens, the potential for improved patient outcomes through tailored interventions becomes increasingly evident.